multiply using the rule for the square of a binomial. (x-10)^2

(x - 10)^2 = (x - 10)(x - 10); = x^2 - 10x - 10x + 100; = x^2 - 20x + 100

Question

Asked 2/26/2013 10:00:17 AM

Updated 7/7/2014 6:19:06 PM

1 Answer/Comment

Rating

3

(x - 10)^2

= (x - 10)(x - 10);

= x^2 - 10x - 10x + 100;

= x^2 - 20x + 100

= (x - 10)(x - 10);

= x^2 - 10x - 10x + 100;

= x^2 - 20x + 100

Added 7/7/2014 6:19:06 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/7/2014 6:35:19 PM]

find the product x(2x+5)^2 **Weegy:**
x(2x+5)^2
x(2x + 5)(2x + 5);
x(4x^2 + 10x + 10x + 25);
x(4x^2 + 20x + 25)
= 4x^3 + 20x^2 + 25x
(More)

Question

Expert Answered

Updated 5/22/2014 11:03:04 AM

0 Answers/Comments

27,077,194

questions answered

There are no comments.